A pre-service art teacher digital literacy framework for digital literacy in pre-service art teacher education in China / Ma Na ... [et al.] - Na, Ma; Lee, Sze Seau Jill; Md Noor, Harrinni; Fu, Jia Qi; Ying, Wang (Universiti Teknologi MARA, 2024)
The Covid-19 pandemic transformed the importance of digital technologies in higher education to a level of necessity and made it possible for teaching and learning to continue during the peak of the pandemic lockdowns all around the world. In the post-pandemic higher education landscape, digital technologies have remained significant tools for teaching and learning. There are many commercial resources for digital technologies, but these resources have not been designed with the professional and pedagogical needs of art teachers in mind. This study addresses the pragmatic educational needs in digital literacy which goes beyond technical skills in digital technologies to encompass abilities in adopting effective digital operations in specific teaching environments, in the context of pre-service art teacher education in China. Intersection of the landscapes for digital technology, national policies in art education, were the identifiable problems addressed. In addition to low frequency and ineffective use of digital technologies in Chinese art education, there are currently no systematic and reliable points of reference for art teachers who are motivated to develop digital literacy in the specialized field of art. This article proposed a Pre-service Art Teacher Digital Literacy (PATDL) framework with a list of principles to guide the design of modules among pre-service art teachers in China. PATDL is informed by a European framework for the digital competence of educators, and applicable principles from computational thinking and media convergence. It is hoped that the framework can guide the design of modules which will enable pre-service art teachers to fully utilize digital technologies with a more informed and comprehensive understanding of their effective use.